Design and synthesis of a phenyl C-glycoside derivative of Spliceostatin A and its biological evaluation toward prostate cancer treatment. Issue 51 (19th December 2019) - Yoshikawa, Yusuke; Ishibashi, Airi; Murai, Kenichi; Kaneda, Yasufumi; Nimura, Keisuke; Arisawa, Mitsuhiro
Graphical abstract: Highlights: Synthetic study of phenyl C- glycoside analogue of Spliceostatin A. An appropriate combination of Julia-coupling reaction as a key step. Phenyl C- glycoside analogue, as a moderate inhibitor for cancer cell growth and AR-V7 expression. Abstract: We designed and synthesized a novel phenyl C -glycoside analogue of Spliceostatin A, which is potent splicing inhibitor and has anti-cancer activities. We successfully synthesized its right phenyl C -glycoside sugar fragment in shorter steps compared to previous synthetic methods for Spliceostatin A and revealed an appropriate fragment combination with a Julia-coupling reaction. Regarding biological activity, the Ph- C -glycoside analogue of Spliceostatin A showed repressed cell proliferation in three prostate cancer cell lines and suppressed AR-V7 expression.